Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Hasil Belajar Membandingkan Pecahan - Rivai, Abd. (Jurnal Kreatif Online, 2016)
Implementations of STAD cooperative learning model to improve learning outcomes, comparing fractions in grade SDN Remote Pebounang. Thesis program of study primary school teacher education, departement of educations, guidance and conseling Tadulako University. Preceptor I Gandung Sugita, preceptor II Bakri Mallo. The result of this study can be seen from the students simply answer the problems associated with learning a given. The implementation of this octivity, the teacher acts as a facilitator and provide guidance to groups who have difficulties in learning, especially in comparing fractions. Students have the opportunity express ideas or opinions related to learning faces. If found students who have difficulty in learning the teacher can guide him to ask questions that lead to the learning process. Essence in this study can give a positive value for the student in understanding the learning presented by teacher. Impressions experienced by studen are : 1) happy following study, at the request of the competent group, 2) students have the ability to express an idea or nation, 3) students can solve problems related to learning fractions because it has constructed knowledge through learning model given, 4) students were satisfied because finding a new learning system that has never been experienced before. Kata Kunci: Kooperatif Tipe STAD; Hasil Belajar; Pecahan